The Emerging WDM EPON - Radivojević, Mirjana; Matavulj, Petar (Springer International Publishing, 2017)
This book proposes dynamic wavelength and bandwidth allocation (DWBA), a hybrid of time-division multiplexing (TDM) and wavelength-division multiplexing (WDM), which offers a solution for service providers faced with multiservice networks. It discusses different models, architectures and implementations and evaluates their performance.
Keywords: Wavelength division multiplexing.; Ethernet (Local area network system); elektronické knihy; electronic books